The EU external policy and the 2015–2018 refugee relocation system in the light of historical institutionalism - Czachór, Zbigniew (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2021)
The main research objective of the text is to analyse the refugee relocation system in the light of historical institutionalism in 2015–2018. Historical institutionalism refers to the interaction between European integration actors in the European Union system, analysed in retrospect from a documentary perspective. The time factor is particularly important, since it enables to follow the institutional process defined by EU norms, procedures and integration rules and their sequential impact on favoured treatment or disavowing of integration visions, preferences, needs and interests. In view of the above, the refugee relocation system proposed and introduced in the period 2015–2018 confirms the above research assumption that the political decision on relocation made by the European Commission and the European Council resulted in a relevant legal act adopted by the EU Council to regulate the issue. Although under the pressure of the situation Member States agreed, some of them began to contest the decisions later.

Głównym celem badawczym tekstu jest analiza systemu relokacji uchodźców w świetle teorii instytucjonalizmu historycznego rozpatrywana w przedziale czasowym 2015–2017. Zastosowany tu instytucjonalizm zwany historycznym, odwołuje się do interakcji pomiędzy aktorami integracji europejskiej w systemie Unii Europejskiej, analizowanych z wykorzystaniem perspektywy dokumentalnej i retrospektywnej. Upływający czas ma tu istotne znaczenie, gdyż pozwala na prześledzenie procesu aktywności instytucji rozumianych także jako normy, procedury i zasady integracji w systemie UE oraz ich sekwencyjnego wpływu na faworyzowanie lub dezawuowanie określonych wizji, preferencji, potrzeb i interesów integracyjnych. Z uwagi na powyższe system relokacji uchodźców zaproponowany i wprowadzony w okresie 2015–2018 potwierdza powyższe założenie badawcze, że to najpierw Komisja Europejska i Rada Europejska podjęły decyzje polityczne o obowiązkowej relokacji, po czym Rada UE ustanowiła w tym zakresie akt prawny, który tę kwestię unormował. Państwa członkowskie pod wpływem presji sytuacji zgodziły się na te decyzje, po czym część z nich zaczęła je kontestować.
Polityka zewnętrzna Unii Europejskiej a system relokacji uchodźców 2015–2018 w świetle teorii instytucjonalizmu historycznego
Keywords: refugee relocation system; historical institutionalism; 2015–2018 period; political decisions on mandatory relocation; situational pressure; system relokacji uchodźców; teoria instytucjonalizmu historycznego; przedział czasowy 2015–2018; decyzje polityczne o obowiązkowej relokacji; presja sytuacji